Quality Improvement Checklist for Nurses in Critical Care Units: Development and Validation - Ritika Rajput; Ashok Kumar Bishnoi; Nipin Kalal; Nikhil Kothari (Journal of Caring Sciences)
Introduction: Patient in critical care units (CCUs) are admitted with multiple clinical problems and busy environment with critical situations makes nurses prone to commit mistakes. Thus, the quality checklist helps the staff in providing adequate, safe, and efficient client care. The objective of the present study was to develop quality improvement checklist for nurses working in CCU. Methods: A methodological study was carried out to develop quality improvement checklist for CCU in different phases. Validity was measured in terms of face, content, and construct validity. Modified Delphi technique used for content validity. Construct validity was analyzed by factor analysis. Reliability was investigated in terms of internal consistency of checklist and inter-rater reliability. Results: There were a total of 32 items in the final draft of the checklist. Cronbach’s alpha which 0.78 was. Cohen’s kappa was 0.88. Inter-item correlation was found between 0.2 and 0.7. The content validity index (CVI) was 0.98. All items were loaded in 8 factors and accounted for 60.7% of variance. Conclusion: Quality improvement checklist has good validity and reliability and it can be used to evaluate and improve the quality of CCU.